Coliphage P1 morphogenesis: analysis of mutants by electron microscopy. - Walker, J T (1983)
We used electron microscopy and serum blocking power tests to determine the phenotypes of 47 phage P1 amber mutants that have defects in particle morphogenesis. Eleven mutants showed head defects, 30 showed tail defects, and 6 had a defect in particle maturation (which could be either in the head or in the tail). Consideration of previous complementation test results, genetic and physical positions of the mutations, and phenotypes of the mutants allowed assignment of most of the 47 mutations to genes. Thus, a minimum of 12 tail genes, 4 head genes, and 1 particle maturation gene are now known for P1. Of the 12 tail genes, 1 (gene 19, located within the invertible C loop) codes for tail fibers, 6 (genes 3, 5, 16, 20, 21, and 26) code for baseplate components (although one of these genes could code for the tail tube), 1 (gene 22) codes for the sheath, 1 (gene 6) affects tail length, 2 (genes 7 and 25) are involved in tail stability, and 1 (gene 24) either codes for a baseplate component or is involved in tail stability. Of the four head genes, gene 9 codes for a protein required for DNA packaging. The function of head gene 4 is unclear. Head gene 8 probably codes for a minor head protein, whereas head gene 23 could code for either a minor head protein or the major head protein. Excluding the particle maturation gene (gene 1), the 12 tail genes are clustered in three regions of the P1 physical genome. The four head genes are at four separate locations. However, some P1 head genes have not yet been detected and could be located in two regions (for which there are no known genes) adjacent to genes 4 and 8. The P1 morphogenetic gene clusters are interrupted by many genes that are expressed in the prophage.